Adherence process from a behavioral analysis perspective. (Brazilian Journal of Behavioral and Cognitive Therapy, 2009)
People's behavior and their contexts have an impact on their quality of life. Adherence behavior patterns involve patients as active subjects, capable of involvement in the process of health and illness. Individuals may learn and maintain effective health behavior, showing adherence to treatment that promotes well-being. A comprehensive understanding of adherence or compliance requires a description of the behavioral relationship between professionals and patients which, in turn, represents the central issue of what is referred to as the communication process. Adherence may be understood as compliance with instructions but it is mainly the result of learning coping responses.
Keywords: Adherence; Communication; Learning; Health Promotion